Development of polyvinyl alcohol-based antioxidant nanocomposite films with nanokaolin impregnated with polyphenols from pomegranate peel extract. (June 2022) - Saroha, Vaishali; Khan, Hina; Raghuvanshi, Sharad; Dutt, Dharm
Abstract: This study aimed to evaluate the potential of polyphenol-modified kaolin as an active nanofiller in the preparation of polyvinyl alcohol-based nanocomposite film for the development of packaging materials.In the first part of the study, polyphenols present in the pomegranate peel were extracted, and their interaction with kaolin clay was investigated through the adsorption process by the UV–VIS method. Adsorption isotherm data were best fitted to the Langmuir model. Moreover, the kinetic study revealed that the trend was in significant agreement with pseudo-second-order. The results showed that the maximum quantity of adsorbed polyphenol on kaolin was 24.96 mg GAE/g of kaolin at 25 °C. Adsorbed polyphenols on kaolin were further characterized by zeta potential, FTIR, and XRD. FTIR analysis showed that polyphenols were adsorbed on kaolin via hydrogen bonding. Zeta potential analysis showed less negative value conforming to the adsorption of polyphenols on kaolin. Intercalation of polyphenols between kaolin platelets was also observed by XRD analysis. For the second part of the study, PP-kaolin nanofiller was incorporated in the composite films. The prepared films were characterized for structural, mechanical, thermal, morphological, and barrier properties. Color and DPPH scavenging activity of films were studied for the appearance and antioxidant activity of the composite films. Total phenolic content of polyphenols released from composite films after 24 h in distilled water and food simulant showed 36% and 27% release of polyphenols into the solvent, thus continuously replenishing the polyphenols onto the food surface. Highlights: Preparation of active kaolin with maximum adsorption of 24.96 mg GAE/g of kaolin at 25 ℃. Adsorption kinetics followed pseudo-second order reaction, and Langmuir model was best fitted with isotherm study. Active kaolin showed controlled release of polyphenols in distilled water and food simulant.